Perlindungan Hukum untuk Menjawab Kecemasan Konsumen dalam Transaksi E-Commerce sebagai Bentuk Kemajuan Teknologi dalam Bisnis - Musthofa, Dion; Apriani, Rani (Peneliti.net, 2025)
This research aims to explore legal protection in e-commerce, focusing on addressing consumer concerns during online transactions. The study employs a normative juridical method with a statutory approach to analyze the relevant regulations, particularly Indonesia's Consumer Protection Act and the Information and Electronic Transactions Act. By reviewing various legal sources and examining real-world cases, the study identifies key challenges faced by both consumers and businesses in e-commerce transactions, including issues of fraud, product mismatch, and inadequate consumer rights protection. The findings suggest that while Indonesian law provides a framework for protecting consumers, its enforcement remains inconsistent, leading to a lack of confidence among consumers. Furthermore, the legal protection afforded in cross-jurisdictional e-commerce transactions relies heavily on the contractual agreements between the parties involved. As a result, the study recommends stronger legal measures to ensure fair treatment and protection for consumers in Indonesia’s growing e-commerce sector.